1986
DOI: 10.1007/bf02359541
|View full text |Cite
|
Sign up to set email alerts
|

Digestibility and effect of copra cake on rate of gain, feed efficiency and protein retention of fattening pigs

Abstract: Sixteen barrows and 16 gilts of average liveweight 40 kg were fed on diets containing 0, 10, 20 or 30% copra cake. The copra cake replaced an equal weight of soyabean-maize meal in the diet. The rates of gain were 705, 719, 543 and 438 g/day and the ratios of feed per unit of gain were 3.21, 3.11, 3.83 and 4.91 for 0, 10, 20 and 30% copra cake diets respectively. Feed intake was reduced when 20 and 30% levels of copra cake were included in the diet. Reduced consumption, digestibility and possibly poor lysine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…The reason for the differences in the ME:DE ratio among CM sources is not known; however, the wide variation in protein digestibility among sources of CM may partly contribute to these differences because the digestible protein concentration in the diet affects urinary N excretion and urinary energy loss, which is the main variable that affects the metabolic utilization of DE for ME (Noblet and van Milgen, 2004). The DE and ME of CM obtained in this experiment are within the wide range of values reported for copra expellers (Lekule et al, 1986;Sauvant et al, 2004;PHILSAN, 2010).…”
Section: Energy Measurements Experimentssupporting
confidence: 86%
“…The reason for the differences in the ME:DE ratio among CM sources is not known; however, the wide variation in protein digestibility among sources of CM may partly contribute to these differences because the digestible protein concentration in the diet affects urinary N excretion and urinary energy loss, which is the main variable that affects the metabolic utilization of DE for ME (Noblet and van Milgen, 2004). The DE and ME of CM obtained in this experiment are within the wide range of values reported for copra expellers (Lekule et al, 1986;Sauvant et al, 2004;PHILSAN, 2010).…”
Section: Energy Measurements Experimentssupporting
confidence: 86%
“…The standardized ileal digestibility (SID) of AA in copra meal and copra expellers fed to pigs ranges between 43 and 81 % [ 11 , 14 16 ]. The SID of Lys in copra meal is also variable, ranging from 51 [ 15 , 17 ] to 73 % [ 10 ], but the SID of all other indispensable AA is greater than that of Lys indicating that the sources of copra meal used in these experiments may have been heat damaged because heat damage will reduce the digestibility of Lys more than that of other AA [ 18 20 ].…”
Section: Copra Meal and Copra Expellersmentioning
confidence: 99%
“…Copra meal and copra expellers may be included in diets fed to growing and finishing pigs by up to 30 % without affecting growth performance [ 22 ], but negative effects of increasing levels of copra meal in the diet have been reported [ 4 , 14 , 23 ]. However, Thorne et al [ 3 ] demonstrated that copra meal can be used by up to 50 % in growing-finishing diets if diets are supplemented with synthetic AA or proteins with higher quality.…”
Section: Copra Meal and Copra Expellersmentioning
confidence: 99%